2021
DOI: 10.48550/arxiv.2105.00266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-driven discovery of Green's functions with human-understandable deep learning

Nicolas Boullé,
Christopher J. Earls,
Alex Townsend

Abstract: There is an opportunity for deep learning to revolutionize science and technology by revealing its findings in a human interpretable manner. We develop a novel data-driven approach for creating a human-machine partnership to accelerate scientific discovery. By collecting physical system responses, under carefully selected excitations, we train rational neural networks to learn Green's functions of hidden partial differential equation. These solutions reveal human-understandable properties and features, such as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, the way in which a scientists extracts information from experiments and observations (data) and encodes that information into PDEs has seen dramatic changes over the last decade, when methods originating in machine learning have started playing an increasingly important role. Currently, there is a rich literature on data-driven discovery of PDEs (see, e.g., [30][31][32][33][34][35][36][37]). The published methods can be loosely di- vided in two classes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the way in which a scientists extracts information from experiments and observations (data) and encodes that information into PDEs has seen dramatic changes over the last decade, when methods originating in machine learning have started playing an increasingly important role. Currently, there is a rich literature on data-driven discovery of PDEs (see, e.g., [30][31][32][33][34][35][36][37]). The published methods can be loosely di- vided in two classes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Rational Neural Networks have superior approximating capabilities. This result is not purely theoretical; in a recent paper on learning Green's functions, [BET21] demonstrated that RNNs learn faster than equivalently sized networks with conventional activation functions. Further, unlike ReLU, rational activation functions are almost-everywhere smooth, meaning that they are suitable for use in PDE discovery.…”
Section: Introductionmentioning
confidence: 96%
“…One advantage of using RNNs is that their poles can reveal information about discontinuities in the network. [BET21] discusses this in detail. Consider an RNN with two input variables, x and t. Fix t = t 0 for some t 0 ∈ R. The function x → U (t 0 , x) for x ∈ C must be rational since the composition of a sequence of rational functions is rational.…”
Section: Introductionmentioning
confidence: 99%
“…It is undoubtedly a fundamental and challenging goal. Many works have studied this from different aspects [9][10][11][12][13][14][15][16]. In general, the establishment of the theory can be divided into two steps: identify the critical variables from observations and connect them by formula.…”
Section: Introductionmentioning
confidence: 99%